2005
DOI: 10.1097/01.mpg.0000181862.59877.bd
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Respond to Hepatitis B Vaccine in Children With Celiac Disease

Abstract: Background: Although IgA endomysial antibodies (EMA) and tissue transglutaminase (TG) are sensitive and specific serologic tests for the diagnosis of celiac disease, there is limited information on the association of the magnitude of antibody level with the severity of the histological abnormalities of the intestine. Purpose: To determine if EMA and TG titers correlate with the severity of histological changes in patients with celiac disease. Methods: We identified 148 children from our laboratory database tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…Certain studies have reported diminished responses of patients with CD to HBV, and attributed this to HLA-DQ2, -DR3, and -DR7 serotypes (2,3). These serotypes (particularly DQ2) are strongly associated with CD, and have been independently linked to the nonresponse to HBV, especially if present in homozygous form (2,3). In our study, DQ2 homozygotes responded equally well as heterozygotes; therefore, we cannot confirm any hypothesis linking diminished immune responses to the DQ2 zygosity.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Certain studies have reported diminished responses of patients with CD to HBV, and attributed this to HLA-DQ2, -DR3, and -DR7 serotypes (2,3). These serotypes (particularly DQ2) are strongly associated with CD, and have been independently linked to the nonresponse to HBV, especially if present in homozygous form (2,3). In our study, DQ2 homozygotes responded equally well as heterozygotes; therefore, we cannot confirm any hypothesis linking diminished immune responses to the DQ2 zygosity.…”
Section: Discussioncontrasting
confidence: 74%
“…Evidence about tetanus vaccine is conflicting (2,8), and immune responses to oral polio vaccine may be stronger in patients with CD (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 95% of celiac patients share one of HLA class II molecules, namely, HLA DQ2, DR3, and B8 haplotypes [14][15][16]. Recently, it has been shown that more than half of the children with CD did not show a response to the standard HBV vaccination, and the rate of nonresponse to HBV vaccine has been reported to be even higher when the adult celiac patients are concerned [17,18]. However, there are few studies addressed to the link between CD and hepatitis B vaccine nonresponse in celiac children [18].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, it has been shown that more than half of the children with CD did not show a response to the standard HBV vaccination, and the rate of nonresponse to HBV vaccine has been reported to be even higher when the adult celiac patients are concerned [17,18]. However, there are few studies addressed to the link between CD and hepatitis B vaccine nonresponse in celiac children [18]. The aim of this study is to assess the response to HBV vaccine prospectively in a group of CD who were on a gluten-free diet (GFD) and to inquire the potential link between CD and hepatitis B vaccine nonresponse by studying shared HLA haplotypes.…”
Section: Introductionmentioning
confidence: 99%